Association of dietary fiber with subjective sleep quality in hemodialysis patients: a cross-sectional study in China - Shuang Zhang; Shu-Xin Liu; Qi-Jun Wu; Zhi-Hong Wang; Hong Liu; Cui Dong; Ting-Ting Kuai; Lian-Lian You; Jia Xiao (Annals of Medicine, 2023)
AbstractBackground Poor sleep quality is a common problem among hemodialysis (HD) patients. Dietary fiber is a key component of a healthy diet and is beneficial for a variety of health outcomes; however, evidence of an association between dietary fiber consumption and subjective sleep quality has not been established among HD patients. Therefore, we determined the association between dietary fiber consumption and the subjective sleep quality in Chinese maintenance HD patients, taking into account fiber type and source.Methods Dietary intake was assessed with a validated food frequency questionnaire in a cross-sectional study including 741 maintenance HD patients between December 2021 and January 2022. The daily intake of dietary fiber was categorized into three groups. The lowest tertile was used as the reference category. Sleep quality of patients was accurately calculated using the Pittsburgh sleep quality index standard questionnaire. Multivariable logistic regression model and restricted cubic spline analysis were performed to assess the relationship between dietary fiber consumption and poor sleep quality.Results Compared with the lowest tertile group of dietary fiber intake, the highest tertile group had a lower prevalence of poor sleep quality. After adjustment for potential confounders, a higher intake of total dietary fiber (ORtertile 3 (T3) to tertile 1 (T1)= 0.51, 95% CI: 0.31–0.85), total insoluble dietary fiber (ORT3 to T1 =0.54, 95% CI: 0.33–0.89), and soluble dietary fiber in vegetables (ORT3 to T1 =0.61, 95% CI: 0.40–0.93) were associated with a lower prevalence of poor sleep quality. Furthermore, significant linear trends were also observed (p < 0.05). No significant interactions were observed in subgroup analyses.Conclusion A higher intake of dietary fiber was inversely associated with the poor sleep quality. These findings support the current recommendations that dietary fiber is essential for health and well-being.